G622 IPE medicine management workshop. (27th April 2016) - Bourke, T; Corkin, D; Cardwell, P; Nugent, J
Abstract : 'Working together across boundaries' (aiming high for education and training) Recognition for higher education and training of children's nurses and medical students implies a need for innovative curricula opportunities. The following project addresses the challenge for healthcare educators to work across boundaries, widening student engagement and participation through inter-professional education (IPE). Creating learning environments whereby student interactions foster the desire to develop shared learning, situational awareness and contribution to patient safety. Overall aim of this two hour 'IPE Drug Prescribing and Administration Workshop' is to facilitate integrated learning and enable medical and nursing students to advance their knowledge and understanding of current best practice. Collectively and individually students become aware of their responsibilities in drug prescribing and administration standards. This IPE workshop was initially implemented in 2007–08 in collaboration with the Centre for Excellence in IPE (Stewart et al, 2010). Additional development of the student workbook and widening engagement with this project is now offering learning opportunities to mental health nursing students since November 2014. Methods: Fourth year medical students alongside third year children's and mental health nursing students are divided into groups of three students, one from each profession. Within their groups, students work together through the written parts of 4 scenarios, referring to BNFC (2015–16) and drug prescription charts before discussing their findings and possible solutions to questions. During feedback, student groups are given the opportunity to demonstrate preparation of medications for administration. They are observed by both medical and nursing facilitators, who provide constructive feedback on aspects of patient safety, decision making skills and an appreciation of the role of healthcare professionals in managing medications safely for infants, children and young people. Results: Students reactions to this integrated learning experience are captured via a Likert-scale questionnaire. Findings confirm that all students identify this work shop as relevant to practice and value identification of common errors in prescribing (NPSA, 2010). Comments include: 'thoroughly enjoyed' and 'more workshops' Conclusion: Students positively engage in this problem-solving exercise, drawing upon their strengths and abilities to learn from each other. This workshop provides a crucial opportunity for exchange of knowledge and fundamental skills for all students involved. Reference: Stewart, M., Purdy, J. Kennedy, N. and Burns, A. An interprofessional approach to improving paediatric medication safety. BMC Medical Education 2010;10 (19):1–7